2017
DOI: 10.3390/ma10060570
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Electrodes Based on Silver Nanowire Networks: From Physical Considerations towards Device Integration

Abstract: The past few years have seen a considerable amount of research devoted to nanostructured transparent conducting materials (TCM), which play a pivotal role in many modern devices such as solar cells, flexible light-emitting devices, touch screens, electromagnetic devices, and flexible transparent thin film heaters. Currently, the most commonly used TCM for such applications (ITO: Indium Tin oxide) suffers from two major drawbacks: brittleness and indium scarcity. Among emerging transparent electrodes, silver na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 75 publications
(137 reference statements)
0
73
0
Order By: Relevance
“…As of today, some degree of control of this inherently stochastic phenomenon has been achieved, permitting to create nanogaps for addressing nanoclusters or single molecules [2][3][4], locally modify the geometry or the material properties to fabricate point contacts [5][6][7], superconducting weak links [8][9][10], nanoheaters [11], plasmonic nanoantennas [12], etc. In addition, recent works also showed that the change of electrical resistance in random networks of conducting nanowires under electric bias can induce percolation in these materials, making them interesting transparent conducting materials suitable in a wide range of applications, as window electrodes, transparent heaters, antennas, etc [13,14]. Besides this rich multipurpose nanofabrication toolbox, controlled EM benefits from the fact that it can be achieved through rather unsophisticated softwares and conventional electronics [6,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…As of today, some degree of control of this inherently stochastic phenomenon has been achieved, permitting to create nanogaps for addressing nanoclusters or single molecules [2][3][4], locally modify the geometry or the material properties to fabricate point contacts [5][6][7], superconducting weak links [8][9][10], nanoheaters [11], plasmonic nanoantennas [12], etc. In addition, recent works also showed that the change of electrical resistance in random networks of conducting nanowires under electric bias can induce percolation in these materials, making them interesting transparent conducting materials suitable in a wide range of applications, as window electrodes, transparent heaters, antennas, etc [13,14]. Besides this rich multipurpose nanofabrication toolbox, controlled EM benefits from the fact that it can be achieved through rather unsophisticated softwares and conventional electronics [6,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…MNW networks have been the subject of a lot of research lately, with a focus on the industrial integration of the networks as transparent electrodes into opto‐electronic devices, as recently reviewed by several authors. [ 20,38,39,157,158 ] Among the possible MNW materials, silver has been the most investigated, [ 33,34,39,159–162 ] while CuNW networks constitute an interesting alternative. [ 48,66,76,163,164 ] Figure 7b exhibits a high‐resolution TEM image of a CuNW showing the fivefold symmetry.…”
Section: The Investigated Materials Technologies For Transparent Heatersmentioning
confidence: 99%
“…This aspect is very important because haziness is a critical parameter for most optoelectronic applications, and such low values are hardly ever achieved with other non‐TCO materials. [ 38 ] This polymer‐based technology made it possible to reach high power densities, up to 10 000 W m −2 (Figure 8d). Heating homogeneity, measured by IR imaging, and extended mechanical stability were demonstrated.…”
Section: The Investigated Materials Technologies For Transparent Heatersmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of 1D nanostructures exist in solar cells, LEDs, chemical sensors, transparent conducting films (TCFs), and heaters to name a few. TCFs, for example, require high conductivity and transparency thus connected networks of 1D nanomaterials have been studied as a viable alternative to thin films of indium tin oxide, which suffer from drawbacks such as brittleness and indium scarcity …”
Section: Introductionmentioning
confidence: 99%